POST HERPETIC NEURALGIA AND OPHTAMOPLEGIA IN PATIENT WITH MULTIPLE SCLEROSIS : A CASE REPORT - Widodo Mardi Santoso; Yeni Quinta Mondiani; Machlusil Husna; Rodhiyan Rachmatiar (Journal of Pain, Headache and Vertigo, 2020)
Zoster Herpes which is also known as ‘shingles’ may cause infection on neuro system through the reactivation of the virus. This infection causes skin eruption along the affected dermatomal distribution and it is called post herpetics neuralgia. This condition occurs on approximately 9-15% patients of zoster herpes who receive no treatment. Elderly women have a higher risk of the condition. Complete oftamoplegia is also related with zoster herpes. It was reported that there were 16 cases in the past one year with a relatively good prognosis (total recovery within 18 months) with an analysis starting from inflammation of trigeminus nervus to cavernosus sinus, cranialis nervus microinfark caused by vasculitis, meningeal inflammation, and demyelinisation (of autopsy). On the other hand, there are theories showing a correlation between zoster herpes infection and multiple sclerosis. Based on the epidemiologic study which has been conducted, that zoster herpes is influencing multiple sclerosis. This virus might induce autoimmune cascade and proinflammatory via particle like Toll – like receptor 4 (TLR-4).